2020
DOI: 10.1155/2020/6450450
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Pulmonary Toxicity in Mice Induced by Exposure to Unflavoured and Apple- and Strawberry-Flavoured Tobacco Waterpipe Smoke

Abstract: The use of flavoured tobacco products in waterpipe smoking (WPS) has increased its attractiveness and consumption. Nonetheless, the influence of flavourings on pulmonary toxicity caused by WPS remains unclear. Here, the pulmonary toxicity induced by plain (P)-WPS, apple-flavoured (AF)-WPS, and strawberry-flavoured (SF)-WPS (30 minutes/day, 5 days/week for 1 month) was investigated in mice. Control mice were exposed to air. Exposure to P-WPS or AF-WPS or SF-WPS induced a dose-dependent increase of airway hyperr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…4 6 12-16 Not only do flavours contribute to attractiveness, the flavouring ingredients, from now on referred to as 'flavourings', can be hazardous too. [17][18][19] Flavoured waterpipe tobacco caused higher toxicity than unflavoured waterpipe tobacco in mice, when looking at different inflammatory and oxidative stress biomarkers. 17 Also, flavourings found in waterpipe tobacco such as limonene, linalool and eugenol are known as being allergenic in human skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 6 12-16 Not only do flavours contribute to attractiveness, the flavouring ingredients, from now on referred to as 'flavourings', can be hazardous too. [17][18][19] Flavoured waterpipe tobacco caused higher toxicity than unflavoured waterpipe tobacco in mice, when looking at different inflammatory and oxidative stress biomarkers. 17 Also, flavourings found in waterpipe tobacco such as limonene, linalool and eugenol are known as being allergenic in human skin.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Flavoured waterpipe tobacco caused higher toxicity than unflavoured waterpipe tobacco in mice, when looking at different inflammatory and oxidative stress biomarkers. 17 Also, flavourings found in waterpipe tobacco such as limonene, linalool and eugenol are known as being allergenic in human skin. 18 Tobacco products, herbal products for smoking and products such as e-cigarettes and e-liquids, are covered by the Tobacco Products Directive 2014/40/EU (TPD).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, it has been shown that WPS induces augmentation of markers of DNA injury including 8-OH-dG and cytochrome P450 1A1 and induces the inhibition of DNA repair genes (46). We have experimentally shown that WPS inhalation in mice can cause DNA injury in various organs including the lung and the heart (18,24,28). It is recognized that DNA damage may cause apoptosis and that caspase-3 is a member of the caspase enzyme family that plays an important role in the execution of apoptosis in COPD (47,48).…”
Section: Discussionmentioning
confidence: 97%
“…The mean numbers of macrophages, neutrophils, and lymphocytes were then changed from per HPF to per mm 2 (1 mm 2 = 4 HPFs). The quantification in all the four studied groups was performed randomly on 10 HPFs in each section (24,25).…”
Section: Histopathologymentioning
confidence: 99%
“…In animal models, exposure to Wp smoke has been shown to cause oxidative damage and subsequent tissue injury to various body organs including the lungs (Khabour et al, 2018;Khan, Sundar, & Rahman, 2018;Nemmar, Al-Salam, Beegam, Yuvaraju, & Ali, 2020a), heart (Al-Sawalha, Al-Filali, Nemmar et al, 2020b), brain (Alqudah, Alzoubi, Ma'Abrih, & Khabour, 2018;Alzoubi, Halboup, Alomari, & Khabour, 2019a, kidney (Al-Sawalha, Alsari, Khabour, & Alzoubi, 2019c;Nemmar et al, 2020c;Rababa'h, Sultan, Alzoubi, Khabour, & Ababneh, 2016), liver (Charab, Abouzeinab, & Moustafa, 2016), and reproductive organs (Ali, 2017;Al-Sawalha, Almahmmod, Alzoubi, Khabour, & Alyacoub, 2019b). These alterations include induction of oxygen-reactive species, lipid peroxidation, and alteration of antioxidative enzyme activities (Badran & Laher, 2020).…”
Section: Discussionmentioning
confidence: 99%